The class with wings - Fleischman, Paul (Cameron Kids, an imprint of ABRAMS, 2024)
"Every afternoon with their heads down and eyes closed, a fourth-grade class embarks on an imaginative migration journey alongside the bird they are studying. Guided by the voice of their teacher in the cool sanctuary of the classroom, the students travel all the way from Brazil to their hometown in Wisconsin. Along the way, they encounter weather, predators, setbacks, and loss. As their imaginations soar, the children begin to relate with their subject; they, too, need rest; have a hard time holding still; and have dodged a bully or two. At the journey's end, the class has learned much more than science and geography--they have learned to fly. In this transcendent picture book, Newberry Medal-winning author Paul Fleischman weaves together a story rich with information, connection, and empathy"--Amazon.com.